ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN MAHASISWA MEMILIH PROGRAM STUDI MANAJEMEN S-1 FAKULTAS EKONOMI UNIKA SANTO THOMAS MEDAN T.A 2020/2021, DALAM KONDISI PANDEMI COVID 19 IMPLIKASINYA PADA PERUMUSAN STRATEGI PROMOSI - Simanihuruk, Peran; Sitompul, Pandapotan (UNIKA Santo Thomas, 2022)
The purpose of this study is to analyze the dominant factors influencing student decision making in choosing the S-1 Management Study Program. With this aim, it is possible to identify what factors dominantly influence student decision making in choosing the Management Study Program at the Faculty of Economics, Unika Santo Thomas, Medan T.A. 2020/2021 in the Covid-19 Pandemic, its implications for the formulation of promotional strategies. The research method used a sample of 125 students, collecting data with questionnaires and documentation and factor analysis techniques. The results of the study, of the 25 factors studied in student decision making to choose the Management study program, it turns out that the most dominant are: Factor 1: Accreditation status, Friends, Teachers, Family, Image / image and campus visits, Factor 2: Ease of work, Success Alumni and Promotional Brochures, Factor 3: Scholarships, Environmental Conditions, Complete Facilities and Building Conditions, Factor 4: Curriculum, Affordable Basic Tuition and Ease of Payment, Factor 5: Family, Education Personnel, Libraries and Lecturers, Factor 6: Alumni Association strong , Webinar Seminar, and Positive Issues and Factor 7: Affordable Cost Per-Credit and Parents' Income. The results of this study are expected to provide a reference as material for consideration in formulating relevant promotions, especially in the COVID-19 pandemic situation for the sake of increasing the number of students in the future. For further research, it is better to add variables that will be used as research variables that are thought to influence students in choosing the Management Study Program.